Effects of Dietary Modified Bazhen on Reproductive Performance, Immunity, Breast Milk Microbes, and Metabolome Characterization of Sows - Geng, Jian; Jin, Weicheng; Hao, Jingyou; Huo, Mohan; Zhang, Yuefeng; Xie, Chunmei; Zhao, Baokai; Li, Yanhua (Frontiers in Microbiology, 2021)
Bazhen is a classics famous prescription for prevention of qi and blood deficiency. The present study aimed to investigate the effects of dietary supplementation with modified Bazhen powder (MBP) on the sows during lactation. Forty pure-bred Yorkshire sows on day 100 of gestation were randomly fed on a standard diet supplemented without (control group) or with 20 g MBP per sow per day (MBP group) during –14 to 7 d relative for parturition. Results showed the serum levels of IL-2, IgA and IgG were higher, while IL-10 level was lower in sows fed with MBP-diet than in controls on day 7 postpartum. A significantly elevated proportion of serum CD4+ T cells and a slightly increase of the ratio of CD4+/CD8+ T cells in the MBP group were also observed. Furthermore, MBP supplementation improved gastrointestinal function of postpartum sows, evidenced by increased levels of motilin, gastrin and NO. UHPLC-QTOF-MS/MS identified a total of 21 absorbed milk components. 16S rRNA gene amplicon sequencing data revealed that the microbiota diversity of the colostrum and transitional milk in the MBP group was increased. At the genus level, relative abundances of enterococcus and anaerostipes were significantly lower in the MBP group on day 0 of lactation. Metabolomic analysis showed that 38 (31) metabolites were upregulated, and 41 (8) metabolites were down-regulated in the transitional milk (colostrum) in response to MBP. Besides, the pathways of metabolic, digestion and absorption, or biosynthesis of amino acids were enriched in the colostrum and transitional milk. Our findings provide new insights into the beneficial effects of MBP, and the microbiota and metabolomics profile of breast milk from sows fed with MBP-diet which should be considered as a potential diet supplementation for lactating sows in pork production.